Interview with Deyfou-lah Sani Bah-Traore on the Togolese Game Origin - the Rise of Dzitri - Kienzl, Lisa; Bah-Traore, Deyfou-lah Sani (Gamevironments, 2019)
In the Togelese game Origin - the Rise of Dzitri that was developed in Lome, the character Edoh takes you on a journey to historic places in the city to revive the spirit of Dzitri. Deyfou-lah Sani Bah-Traore, programmer and game developer, spoke with Lisa Kienzl about his and his Teammate s work on Origin - the Rise of Dzitri
Accepted: 2020-03-25T23:30:30Z
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Video Games and the Global South - Penix-Tadsen, Phillip (ETC Press, 2019)
Redefines games and game culture from south to north, analyzing the social impact of video games, the growth of game development and the vitality of game cultures across Africa, the Middle East, Central and South America, the Indian subcontinent, Oceania and Asia.
OCLC: 1104212185
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Towards Diversity: Interventions in Curriculum and Pedagogy of an Introductory Game Design Course - Hanli, Geyser (DiGRA/FDG '16 - Abstract Proceedings of the First International Joint Conference of DiGRA and FDG, 2016)
Transformation and the decolonization of the curriculum, modes of teaching, and classroomare key concerns in South African Higher Education. In game design education this need is exacerbatedby the slow pace of diversification in both academia and the industry.This paper presents a close analysis of interventions undertaken into an introductory game design course to address the difficultiesof diversification across racial, genderand economic divides. The results of the interventions are assessed, and recommendations for future adjustments to the course in aid curricular decolonization is are made.
Place: Dundee, Scotland
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Autrice; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé